PROVIDING ECONOMIC EFFICIENCY BY IMPROVING THE LABOR PROTECTION SYSTEM IN MANUFACTURING ENTERPRISES - Sadiqkhojaev Kamoliddin Jaloliddinovich (Labor economics and human capital, 2023)
This article discusses how to properly manage production resources, including human capital, to ensure economic efficiency in material production enterprises and achieve a positive result, as well as the emergence of unexpected risks associated with production at the enterprise during this period of management, and their negative impact . on economic efficiency. At the same time, the issues of determining appropriate measures to eliminate these unexpected risks and thereby ensure the economic efficiency of the production enterprise were analyzed.